Sema family met at home of Don & Lina Cash (Raton Range Raton, New Mexico, 1980)
Newspaper Article on the Sema family reunion.
Master list item #: 21
File location is in the Raton File Cabinet
Keywords: Cash, Don; Cash, Lina; Sema, Joe; Sema, Norma; Sema, Andy; Stadjuhar, Ivan; Sema, Frank; Vincioni, Elizabeth; Vincioni, Elizabeth; Hicks, Lesleigh; Hicks, Wendell; Sluga, Hester; Collins, Mary; Collins, Fritz; Gaskin, Mary; Gaskin, Willie; Peryatel, Albert; Peryatel, Jan; Peryatel, Iris; Peryatel, Jack; Peryatel, Beulah; Slavic, Pauline; Ridolfi, Elvira; Gaskin, Lena; Peryatel, Arthur; Peryatel, Isabelle; Stadjuhar, Mary; Stadjuhar, Robert; Stadjuhar, Carrie; Penjuv, Mary Sluga; Sluga, Nellie; Pavicich, Rose; Sluga, Frank; Sema, Joe; Local History; Biography; Life and Customs; Family; Reunion; Raton, New Mexico; Winslow, Arizona; Aluquerque, New Mexico; Canyon, Texas; Colorado Springs, Colorado; Las Cruces, New Mexico